Essential drug dosage calculations - Hegstad, Lorrie N.; Hayek, Wilma (Upper Saddle River, New Jersey : Prentice-Hall, 2001)
Helping nursing students master the critical knowledge they will need to accurately prepare and administer safe medications, this text provides a concise method to help them develop competence in interpreting medication orders and calculating safe medication dosages.
1. Basic Arithmetic. -- 2. Metric System of Measurement. -- 3. Apothecaries' and Household Systems of Measurement. -- 4. Interpretation of Medication Orders and Labels. -- 5. Use of the Proportion Formula to Calculate Equivalent Units of Measure. -- 6. Checkpoint. -- 7. Calculation of Oral Medications. -- 8. Parenteral Drugs in Solution. -- 9. Powder and Crystalline-Form Drugs. -- 10. Checkpoint. -- 11. Insulin Dosage Calculations. -- 12. Calculation of Intravenous Fluids and Medications. -- 13. Advanced Intravenous Calculations. -- 14. Calculating Dosages for Infants and Children. -- 15. Exams.
Includes index.
Keywords: DRUGS -- DOSAGE